An analysis of the Gayatri mantra as a mega-compression: A cognitive linguistic perspective in light of conceptual blending theory - Naicker, Suren (HTS teologiese studies, 2019)
In this article, the Gayatri mantra, one of the most sacred chants to be found in Hindu lore, will be analysed as a blend, where an entire philosophy is compressed into these few syllables, which will be expounded upon here in more detail. Drawing upon insights from conceptual blending theory, this sacred mantra will be unpacked and explored, and it will be shown here that this ancient Rigvedic hymn is actually a nucleic compression which once tapped into leads the practitioner to new insights and higher levels of spiritual awareness as the inner meaning unfolds. Practising Hindus around the world revere and recite this mantra with the utmost reverence, and this is true of the Indian diaspora in South Africa as well. Aside from presenting this hymn through the lens of blending theory, the aim is to demonstrate and explain why exactly this mantra is chanted with such reverence and given precedence over the many other mantras found throughout the Vedic texts.